Analyzing conflict in a short story christmas every day by William Dean Howells - Angelica, Evania; Laksminy, Luh Putu; Ediwan, I Nyoman Tri; Mulyana, Novita (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2024)
Conflict is an issue that will be experienced by many people and everyone doesn’t want any single conflict to happen in their lives. Not only in our everyday lives, conflict can also be found in literary works as the characters in the works are humanlike. This study aims to discover the types of conflict in a short story called Christmas Every Day. This qualitative descriptive study utilized the library research method to collect data, which requires a process of reading books, journals, and other references to have a thorough understanding of the topic. In addition, note-taking technique was also utilized in the process of data collection. Afterward, the data was then evaluated using a conflict theory presented by Nurgiyantoro (2018). He proposed two types of conflict, internal conflict and external conflict. The findings of the study show some internal and external conflicts in the short story. One data was found to reflect internal conflict occurred and three data were classified as physical conflict undergone by the character in the short story. However, social conflict, which is a classification of external conflict, cannot be found in this short story.